Childhood-Onset Epileptic Encephalopathy Associated With Isolated Focal Cortical Dysplasia and a Novel TSC1 Germline Mutation. (May 2018) - Hoelz, Hannes; Coppenrath, Eva; Hoertnagel, Konstanze; Roser, Timo; Tacke, Moritz; Gerstl, Lucia; Borggraefe, Ingo
Tuberous sclerosis complex (TSC) is an autosomal-dominant inheritable neurocutaneous disease due to mutations within the TSC1 and TSC2 genes. Many patients present with West syndrome, a severe epilepsy syndrome characterized by the triad of infantile spasms, an interictal electroencephalogram (EEG) pattern termed hypsarrhythmia (continuous slow activity with an amplitude higher than 300 µV and multiregional spikes/polyspikes/sharp waves) and developmental regression. In this study, we report on a previously healthy patient with positive family history of epilepsy with new-onset epileptic encephalopathy at the age of 9 years. Clinical signs alone were not sufficient to establish the diagnosis of TSC but epilepsy panel screening revealed a novel frameshift mutation (c.90delA; p.Glu31Argfs*12) within the TSC1 gene. Segregation gene analysis detected the same mutation in the mother. Cranial magnetic resonance imaging (MRI) studies from the index patient and his mother revealed a similar pattern of isolated subcortical white matter lesions resembling most likely focal cortical dysplasia (FCD) type IIb. In summary, in these 2 related patients, a novel TSC1 frameshift mutation was associated with an isolated FCD type IIb in the absence of further CNS abnormalities usually encountered in patients with TSC, fostering our understanding of the broad mutation spectra in the TSC1 gene and the close relationship between cortical tubers and FCD type IIb.